Supporting farmer and fisher communities in Wales through uncertainty: two mixed methods studies. (20th October 2021) - Davies, AR; Grey, CNB; Homolova, L
Abstract: Background: Rural, farming and fishing communities in Wales were highlighted as vulnerable to uncertainty and change from Brexit, with likely impacts to mental health and wellbeing in these groups. Policy needs to understand how to prevent challenges, protect against health impacts, and promote mental health and wellbeing in these hard-to-reach/engage groups using evidence-based solutions. Methods: Two mixed-methods studies were undertaken in 2019-20, using identical methodologies, one in farming and one in fishing communities. For both, MEDLINE, Embase, PsycINFO, NICE, and Cochrane databases were searched for keywords associated with farmers/fishers, mental health, wellbeing, resilience, support, and suicide; for studies of any design published in English, in 2005-19. Evidence was further supported by stakeholder engagement through two world café workshops in each group (farmers n = 19, fishers n = 13). For farmers, additional face-to-face and telephone consultation took place (n = 26). Challenges, existing support, and relevance of the evidence review were examined. Engagement was recorded through researcher's field notes and analysed thematically. Results: For farmers, 843 records were identified after duplicated removed, screened, 130 full text records examined, and 14 interventions included. For fishers, 415 records identified, 135 full text examined, and 7 interventions included. Evidence-based programmes supporting farmers were centred on health promotion, mental health literacy, and cross-agency partnership development; and for fishers, support was centred solely on health promotion. Qualitative engagement uncovered challenges faced in Wales, barriers to seeking support, and assets available to each group. Conclusions: The evidence from the review and engagement was brought together to create action frameworks for supporting both farmers and fishers in Wales, centred on prevention, protection, and promotion of mental health and wellbeing. Key messages: Farming and fishing are contributors to Wales' rural economy and cultural identity. A strong evidence-base of how to support mental health of these groups is vital to help them cope with change. Action for supporting both farmers and fishers in Wales should be centred on prevention, protection, and promotion of mental health and wellbeing.